Implementation of Hazard Analysis Critical Control Point Nutrition Service at Toto Kabila Regional Public Hospital, Bone Bolango (KEMAS: Jurnal Kesehatan Masyarakat, 2019)
Hospitalized patients are very susceptible to various food-borne diseases. Food management in the hospital needs more careful attention. Hazard Analysis Critical Control Point (HACCP) is a preventive control system based on identification of critical points in the management and production of food as a way to ensure food safety. The objective of this study is to identify the implementation of HACCP principles in nutritional and dietetic service of RSUD Toto Kabila, Bone Bolango. This qualitative study employed descriptive survey method with HACCP as the study focus. The informants consist of eight people; three people as key informants and five people as triangulation informants obtained by purposive sampling. Data were analyzed using Miles and Huberman method, in which the collected data was written as matrix and then as checklist. The result revealed that nutrition and dietetics of RSUD Toto Kabila Bone Bolango was yet to implement HACCP according to the national standard (without documentation). This issue attributed lack of facilities and human resources at the department. It is suggested that the hospital implements HACCP according to the Indonesian National Standard as well as provides supporting facilities.